Islam Mein Pani Ka Intazam - Edited by Farooqi, Nasir I; Biswas, Asit K; Bino, Murad J (Oxford University Press Karachi, 2006)
On water supply management according to Islam and water management in various Islamic countries.
Keywords: Water resources development--Government policy -- Water-supply--Management -- Africa, North